Back-to-Back Comparison of Colonoscopy With Virtual Chromoendoscopy Using a Third-Generation Narrow-Band Imaging System to Chromoendoscopy With Indigo Carmine in Patients With Lynch Syndrome. (October 2019) - Cellier, Christophe; Perrod, Guillaume; Colas, Chrystelle; Dhooge, Marion; Saurin, Jean-Christophe; Lecomte, Thierry; Coron, Emmanuel; Rahmi, Gabriel; Savale, Camille; Chaussade, Stanislas; Bellanger, Jérôme; Dray, Xavier; et al.
Abstract : INTRODUCTION: Colonoscopic screening with indigo carmine chromoendoscopy (ICC) in patients with Lynch syndrome (LS) improves the adenoma detection rate but is time consuming and poorly used in clinical practice. Narrow-band imaging (NBI), a virtual chromoendoscopy technique, highlights superficial mucosal vessels and improves adenoma characterization. We conducted a prospective multicenter trial in a back-to-back fashion to compare the third-generation NBI with ICC for detecting colonic adenomas in patients with LS. METHODS: In a multicenter, prospective, noninferiority trial, 138 patients underwent a double colonoscopy, first with NBI, followed by ICC, in a back-to-back design. The primary noninferiority outcome measure was the number of patients with at least one adenoma after NBI compared with the number of patients with at least one adenoma after NBI and ICC. RESULTS: The 138 analyzable patients were all proven mismatch repair mutation carriers for LS (MLH1 = 33%, MSH2 = 47%, MSH6 = 15%, PMS2 = 4%, and EPCAM = 1%). The mean age (SD) was 40.5 (14.7) years, and 64 (46.4%) were men. The median withdrawal time for an NBI procedure was 8 minutes (interquartile range 6–11) compared with 13 minutes (interquartile range 8–17) for ICC. At least one adenoma was detected during the initial NBI pass in 28 patients (20.3%), and 42 patients (30.4%) had at least one adenoma detected after both NBI and ICC (difference, 10.1%; 95% confidence interval, −0.1%–20.3%); this represents an increase of 50.0% of the adenoma detection rate. ICC detected additional adenomas in 25 patients (18.1%). DISCUSSION: Colonoscopy combining NBI and ICC detects more adenomas than third-generation NBI alone in patients with LS, respectively, 30.4% vs 20.3% (difference, 10.1%; 95% confidence interval, −0.1 to 20.3), thus failing the noninferiority assumption of NBI compared with combined NBI and ICC. Although less time consuming, colonoscopy using the third-generation NBI cannot be recommended to replace ICC in patients with LS.